Product Heterogeneity, Within-Industry Trade Patterns, and the Home Bias of Consumption? - Raphael Auer (Swiss National Bank, Study Center Gerzensee, 2009)
Starting with Krugman (1980), much literature has analyzed how trade liberalization affects the economy based on the notion that trade is motivated by consumer's love of variety. In this paper, I augment these preferences by the determinants of demand for heterogeneous products. The model features products with heterogeneous attributes and consumers with heterogeneous tastes for attributes. Allowing for international trade, the model predicts a within-industry home market effect, i.e., that high domestic demand for an attribute leads to entry of firms producing a fitting output and, consequently, net exports of products embodying the attribute. Second, the model rationalizes why consumption is home-biased in the short run. Each country's industry is optimized for the preferences of domestic consumers and thus somewhat inappropriate for the export market. Third, in the long run, countries specialize further and the within-industry home market effect intensifies. Intriguingly, (as long as it is incomplete) this specialization implies that the home bias disappears completely, thus demonstrating that Linder's (1961) conjecture describes a temporary phenomenon that does not prevail in general equilibrium.
Keywords: F12; F15; L15; L16; 330; Intra-Industry Trade; Monopolistic Competition; Firm Dynamics; Product Heterogeneity; Industrial Structure; Produktdifferenzierung; Intraindustrieller Handel; Unternehmenserfolg; Industriestruktur; Privater Konsum; Monopolistischer Wettbewerb; Theorie